Lymphangiomyomatosis discovered by massive hemoptysis during general anesthesia -A case report- - Deokkyu Kim (Korean Journal of Anesthesiology, 2012)
Lymphangiomyomatosis (LAM) is a rare lung disease that is characterized by the progressive proliferation of atypical smooth muscle-like cells, which leads to severe respiratory impairment and death. Dyspnea, cough, recurrent pneumothorax, and hemoptysis are the most common clinical symptoms of LAM. We report a 29-year-old female patient with massive hemoptysis during laparoscopic gynecologic surgery under general anesthesia, who was diagnosed with pulmonary LAM.